1994
DOI: 10.1111/j.1460-9568.1994.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Archistriatal Lesions Impair the Acquisition of Filial Preferences During Imprinting in the Domestic Chick

Abstract: The avian archistriatum has been demonstrated to play a role in agonistic behaviours and avoidance learning. However, the extent of its role in learning is unknown. The involvement of the archistriatum in the learning process of filial imprinting was therefore investigated in day-old chicks. Bilateral archistriatal lesions, lateral cerebral area lesions or sham archistriatal penetrations were made in dark-reared, day-old chicks, which were subsequently exposed to either a rotating red box or blue cylinder for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In mammals, the amygdala has an important role in the expression of (conditioned) fear (e.g., discussion in Davis et al, 1994). In chickens, the amygdaloid part of the archistriatum forms part of the system for filial imprinting (Lowndes et al, 1994). In an evoked potential study, Phillips (1966) showed that there is no multisensory but only visual input to this part of the archistriatum.…”
Section: Functional Considerationsmentioning
confidence: 98%
“…In mammals, the amygdala has an important role in the expression of (conditioned) fear (e.g., discussion in Davis et al, 1994). In chickens, the amygdaloid part of the archistriatum forms part of the system for filial imprinting (Lowndes et al, 1994). In an evoked potential study, Phillips (1966) showed that there is no multisensory but only visual input to this part of the archistriatum.…”
Section: Functional Considerationsmentioning
confidence: 98%
“…The information integrated in the IMM is mainly transmitted to the amygdala, then to a dopaminergic nucleus, the medial striatum (MSt, formerly referred to as the lobus parolfactorius) Davies et al 1997;Schnabel et al 1997;Csillag 1999;Matsushima et al 2001;Metzger et al 2002). The amygdala and MSt are crucial for imprinting (Lowndes et al 1994;Izawa et al 2001), and some regions of the nidopallium receive input from the dopaminergic neurons of the MSt (Schnabel et al 1997;Metzger et al 2002). Thus, although the afferent pathways into the VW and the efferent pathways from the IMM are well defined, the anatomical connection between the VW and IMM were only recently clarified.…”
Section: Telencephalic Neural Network Essential For Visual Imprintingmentioning
confidence: 99%
“…The amygdala and MSt are crucial for imprinting (Lowndes et al . ; Izawa et al . ), and some regions of the nidopallium receive input from the dopaminergic neurons of the MSt (Schnabel et al .…”
Section: Introductionmentioning
confidence: 98%
“…The medial hyperstriatum ventrale in chicks has been implicated in filial imprinting and one-trial passive-reward learning [Rose, 1991]. Reciprocal connections between the hyperstriatum ventrale and the amygdala in birds lend some credence to the idea that the amygdala plays a role in motivational aspects of the learning process [Lowndes et al, 1994].…”
Section: Hyperstriatal Projectionsmentioning
confidence: 99%